2020
DOI: 10.35631//ijham.39002
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainability of Flora, Fauna and Geometric Motif Designs Among Batik Tulis Manufacturers in Klang Valley

Abstract: The purpose of this research is to find out the development of the batik tulis industry in the Klang Valley from the 1970s until 2018. It aims to study the design and identity of the batik tulis motif and patterns. This research used several methods and approaches for data collection which consisted of interviews, observations, and photo documentation. Three batik tulis manufacturers in the Klang Valley have been selected for this study. The data collected were then analysed using an analytical design approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…All eight studies used a qualitative approach, in which three of them conducted fieldwork (Kari et al, 2019(Kari et al, , 2020Sobri & Legino, 2020) and one study used MATLAB and Adobe Illustrator for design purposes (Mustapha et al, 2020). Meanwhile, another two utilised case studies (Abdullah, 2020;Abdullah & Samin, 2020) and one utilised systematic observation (Wan Bakar et al, 2021a). For data collection, all the studies used observational approach.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All eight studies used a qualitative approach, in which three of them conducted fieldwork (Kari et al, 2019(Kari et al, , 2020Sobri & Legino, 2020) and one study used MATLAB and Adobe Illustrator for design purposes (Mustapha et al, 2020). Meanwhile, another two utilised case studies (Abdullah, 2020;Abdullah & Samin, 2020) and one utilised systematic observation (Wan Bakar et al, 2021a). For data collection, all the studies used observational approach.…”
Section: Methodsmentioning
confidence: 99%
“…The meta-analysis of the eight articles identified that the subject was divided into few categories, which are commercial batik (Wan Bakar et al, 2021a), contemporary batik (Wan Bakar et al, 2021b), batik Tulis (Abdullah, 2020;Abdullah & Samin, 2020), batik Sarong (Sobri & Legino, 2020), batik block (Kari et al, 2019(Kari et al, , 2020Mustapha et al, 2020), and commercial batik (Shaari & Abd Rahman, 2017). These research projects examining the batik design originated from different locations in Malaysia (Mustapha et al, 2020), including Melaka (Wan Bakar et al, 2021aBakar et al, , 2021b, Klang Valley (Abdullah, 2020;Abdullah & Samin, 2020), and Terengganu (Kari et al, 2019(Kari et al, , 2020Sobri & Legino, 2020) (see Table 5).…”
Section: Subjects Categories and Locationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lasem batik is one of the ancestral heritages which is an acculturation between Java and China (Roziqin et al, 2021). Currently, Batik Tulis Lasem is experiencing a fairly extensive marketing development and is even exportoriented (A. H. Abdullah & Samin, 2020). Some of Lasem's Batik Tulis MSMEs are members of the Sarwo Endah KUB with more than 20 Batik Tulis MSMEs members.…”
Section: Introductionmentioning
confidence: 99%